Penetapan Kadar Simultan Deksametason dan Metilprednisolon dengan Metode Kromatografi Gas Spektrometri Massa melalui Derivatisasi - Swasono R. Tamat; Ernawati Ernawati; Linda Rosalina; Sonny Pujianto (JURNAL ILMU KEFARMASIAN INDONESIA, 2006)
This investigation is intended to find a simultaneous assay method for glucocorticosteroids declared as doping compound by the International Olympic Committee. Experiments were carried out in the determination of dexamethason and methylprednisolon in urine matrix by gas chromatography-mass spectrometry (GC-MS) using various derivatisation reagents, reaction temperature and time. Selection of the best derivatisation reagent was based on the separation of total ion chromatogram (TIC) and appearance of three characteristic ions, m/z 305, 345,680 or m/z 206,456, 662 for dexamethasone; and m/ z 279, 369, 459 or m/z 147, 424, 644 for methylprednisolone. Dexamethasone and methylprednisolone derivates in the GC-MS spectra were identified by characteristic ions of m/z 305 (dexamethasone) and m/ z 279 (methylprednisolone). The best derivatisation yield was achieved by a combination of TMSI - [BSTFA-TMCS (99:1)](2:1) reacted at 90°C for 90 minutes, which produced a linear correlation between concentration (0-150 ng/ml ) and ratio of quantitation-ion abundance of standard compound/ion abundance of D3-testosterone internal standard with r= 0.9937 for dexamethasone and r=0.9823 for methylprednisolone; high precision CV=12.14% (dexamethasone) and CV=13.87%(methylprednisolone); high recovery for both dexamethasone and methylprednisolone, and LOD values of 4,44ng/ml (dexamethasone) and 1.80ng/ml (methylprednisolone). The method can be used for simultaneous quantitative assay of glucocorticosteroids, and has been validated for ten other glucocorticosteroid compounds.